Research of Test Method of Single Tooth Bending Fatigue Loading of Involute Helical Gear - Nan Feng; Jingcai Zhang; Jinfeng Li; Man Cheng (Jixie chuandong)
For the problem of bending fatigue strength test of involute helical gear, the change regulations of bending stress and load distribution relation of helical gears with different tooth width and helical angle are researched by using RomaxDesigner. The contact line positions and the maximum stress are got, and it can be used to determine the loading position and load of helical gear in single tooth bending fatigue test. The simulation values of bending stress of different helical angle gears and the calculated values obtained by a series of correction coefficients in GB/T 3480—1997 are compared and analyzed. It is found that there is a big difference between them, which proves the necessity of bending fatigue test of helical gear. The test scheme of helical gear bending fatigue strength is raised. The results of helical gear bending fatigue test according to the method can be transformed into the national standard, which can be used in future to improve the accuracy of evaluating helical gear bending strength.